Utilization of epiphytes by birds in a Brazilian Atlantic Forest - Cestari, Cesar [UNESP]; Pizo, Marco Aurelio (Neotropical Ornithological Soc, Usgs Patuxent Wildlife Research Ctr, 2008)
Epiphytes constitute a great part of the vegetation biomass in Neotropical forests, offering a large variety of resources to birds. Despite their structural and ecological importance, few studies investigated the use of epiphytes by birds in the Neotropical region. We studied the bird species that exploit vascular epiphytes (and hemi-epiphytes) in an Atlantic forest site in southeastern Brazil. The resources exploited, seasonal variation in the use of epiphytes, the frequency of foraging and selectivity in epiphytes, and the relationship between the use of epiphytes and the participation in mixed-species bird flocks were investigated. After 360 h of observations along trails crossing the forest, 24 bird species (12 families) were recorded in a total of 74 events of epiphyte exploitation. Thamnophilidae (four species), Trochiliclae, Thraupidae and Furnariidae (three species) were the richest bird families in our sample, while Furnariidae and Dendrocolaptidae were the more frequently recorded families. Plants in the Bromeliaceae and Araceae families were the most abundant and more frequently exploited epiphytes. Nectar, water, nest material and invertebrates were the most frequently exploited resources, mainly from Bromeliaceae. None of the species for which we had enough data revealed to be a frequent user of epiphytes for foraging or selective to any epiphyte group. The White-eyed Foliage-gleaner (Automolus leucophthalmus; Furnariidae), a common participant of understory mixed-species flocks, exploited epiphytes more frequently when associated with mixed-species flocks. The utilization of epiphytes was opportunistic for most of the bird species recorded and occurred throughout the year with no seasonal variation.
Keywords: Atlantic forest; epiphytes; mixed-species flocks; foraging specialization